Perceived Academic Code of Ethics: A Research on Turkish Academics - YILDIZ ŞEN, MÜGE LEYLA (ELSEVIER SCIENCE BV, 2013)
Ethics is a difficult and controversial concept. Many businesses and nearly all professions have a code of ethics. The existence of a code of ethics in a profession means that unethical behaviour may not be allowed or tolerated. Thus, members of a profession do not display their unacceptable behaviour. Code of ethics for academics is distinct from moral codes that may apply to the culture, education, and religion of a whole society. Academics play the role of educators, researchers, administrators, consultants, professional colleagues, and professors. This article tries to identify a code of ethics for academics in their role as educators/teachers. There is a lack of Turkish academic code of ethics. Thus, the research sample is consisted of 100 academics employed in both public and private universities in Istanbul. We used the five point scales of The Statement on Professional Ethics for academics developed by AAUP and refined by AOM and AMA. Based on the analysis, we identified the hypernorms related to academics in their role as educators. Thus, behaviours deemed ethically unacceptable by the community of academics in Istanbul. Turkey were identified and discussed. (C) 2013 The Authors. Published by Elsevier Ltd. Open access under CC BY-NC-ND license.
Keywords: Professional ethics; Code of ethics for academics; Ethics; SOCIAL-RESPONSIBILITY; MARKETING EDUCATOR; PROFESSIONAL CODES; CORPORATE CODES; CONDUCT